KAJIAN FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN (Studi Pada Toko Elegan Shoes Bukittinggi) : STUDY OF FACTORS AFFECTING THE PURCHASE DECISION (Case of Elegant Shoe Store in Bukittinggi) - Afrizal Afrizal; Henmaidi Henmaidi (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine and analyze what factors can influence a Purchase Decision (study at Elegant Soes Bukittinggi store). The population in this study are customers who have shopped at the Elegant Shoes store, especially those who live in the city of Bukittinggi with a total sample of 100 respondents who were taken using the Purposive Sampling technique. Primary data collection uses questionnaires distributed to customers who have shopped at the Elegant Shoes store and secondary data collection uses literature studies from reading sources such as books, journals, websites and articles related to research. The results of hypothesis testing in this study state that all hypotheses can be accepted, where the Consumer Behavior variable has a positive and significant effect on the Purchasing Decision variable. This Purchase Decision identifies that the higher the usefulness of the product and the suitability of the product to the consumer's purchase value, the higher the value of the purchase decision and the Online Promotion variable has a positive and significant effect on the Purchase Decision variable, this indicates that the higher the intensity of online promotions carried out by the Elegant Shoes store it can improve the purchasing decisions made by consumers.